Pengaruh urea terhadap pertumbuhan dan kandungan nutrisi Spirulina platensis - Arifin, Nasrullah Bai; Putra, Ahmad Pradana Rachmadian; Widyawati, Yuni; Hariati, Anik Martinah (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Spirulina platensis is a highly nutritious cyanobacterial microalga. This microalga is rich in protein, vitamins, minerals and antioxidants. The use of media and cultivation methods that are not appropriate can affect the nutritional content of this microalgae. This study aims to evaluate the effect of urea on growth, biomass production, nutrient content and pigments of S. platensis on an outdoor scale. Technical media such as urea are used instead of nitrate in standard media (zarrouk). This study used four treatments with three replications. The treatments used were different doses of urea, namely 0.1 g/L, 0.4 g/L, 0.7 g/L, and 1 g/L. The results showed that the use of urea affected the growth and nutritional content of S. platensis. The use 0.4 g/L urea producued comparable results than that of nitrate as nitrogen source. However, phycocyanin content was still lower than nitrate-based media. Inconclusion that urea was potential alterative nitrogen source for spirulina cultivation.